A Performance Comparison of User and Access Point based Artificial Immune Systems for intrusion detection on a Wireless Local Area Network - Akbal, Erhan; Ergen, Burhan (Int Journal Computer Science & Network Security-Ijcsns, 2007)
Rapidly increasing wireless network systems and growing up of the mobile applications is raised threatening component for the security. The firewalls, virus software and protecting software is not capable to protect the network for a long time, because the use and misbehavior is continuously increasing and the network operates may be late to take precautions. This study aims to detect and protect the networks by using an Artificial Immune System (AIS) while removing the insufficient other protective approaches. The presented approach is not always requiring an operator interfere while keeping the high performance of the Wireless Local Area Network (WLAN) and network equipment. In presented study, the access point based AIS is realized on the contrary to classical methods detecting the intrusion on all node. It is observed the proposed method exhibit the higher performance than classical method.
Keywords: Artificial Immune System; Intrusion Detection; Wireless Network Security